The Hope of Heavenly Healing of Disability, Part 2, Philosophical Issues - Gould, James B. (Journal of disability & religion, 2017)
This is Part 2 of a two-part article. The elimination view affirms that the disabled will be healed in heaven. While its theological credentials are strong, the elimination view faces philosophical difficulties - epistemic problems (it is said to misjudge the badness of life with disability), moral problems (it is said to express discriminatory attitudes to people with disabilities), and metaphysical problems (it is said to disrupt the personal identity of people with disabilities). In this article, the author defends the elimination view from these charges.